Electrical parameters and water permeability properties in monolayers formed by epithelial cells cultured on permeable supports - Ozu, Marcelo (2005)
T84 is an established cell line expressing an enterocyte phenotype whose permeability properties have been widely explored. Osmotic permeability (POSM), hydraulic permeability (PHYDR) and transport associated net water fluxes (JW-transp), as well as short-circuit current (ISC), transepithelial resistance (RT), and potential difference (ÄVT) were measured in T84 monolayers with the following results: POSM 1.3 ± 0.1 cm.s-1 x 10-3; PHYDR 0.27 ± 0.02 cm.s-1; RT 2426 ± 109 Ù.cm2, and ÄVT 1.31 ± 0.38 mV. The effect of 50 ìM 5,6-dichloro-1-ethyl-1,3- dihydro-2H-benzimidazol-2-one (DCEBIO), a “net Cl- secretory agent”, on T84 cells was also studied. We confirm the reported important increase in ISC induced by DCEBIO which was associated here with a modest secretory ÄJW-transp. The present results were compared with those reported using the same experimental approach applied to established cell lines originating from intestinal and renal epithelial cells (Caco-2, LLC-PK1 and RCCD-1). No clear association between PHYDR and RT could be demonstrated and high PHYDR values were observed in an electrically tight epithelium, supporting the view that a “water leaky” barrier is not necessarily an “electrically leaky” one. Furthermore, the modest secretory ÄJW-transp was not consistent with previous results obtained with RCCD-1 cells stimulated with vasopressin (absorptive fluxes) or with T84 cells secreting water under the action of Escherichia coli heat stable enterotoxin. We conclude that, while the presence of aquaporins is necessary to dissipate an external osmotic gradient, coupling between water and ion transport cannot be explained by a simple and common underlying mechanism.